2021
DOI: 10.3892/ol.2021.13041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of soluble tissue‑derived biomarkers from human thyroid tissue explants maintained on a microfluidic device

Abstract: Although a large cohort of potential biomarkers for thyroid cancer aggressiveness have been tested in various formats in recent years, to the best of our knowledge, thyroglobulin and calcitonin remain the only two established biomarkers associated with thyroid cancer management. Our group has recently validated a novel means of maintaining live, human ex vivo thyroid tissue within a tissue-on-chip format. The present pilot study aimed to interrogate the tissue effluent, containing all the soluble markers relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…These are well-known patterns that indicate that cell plasma membranes were intact during tissue incubation in the device. 24,[26][27][28][70][71][72] Secondly, we showed that the cytokines released by GBM tissues in the device remained the same for the duration of the experiment. We assayed the levels of 105 cytokines in the effluents corresponding to days 2, 4 and 8 of incubation.…”
Section: Maintaining Fresh Gbm Biopsies In a Viable Condition In The ...mentioning
confidence: 70%
See 2 more Smart Citations
“…These are well-known patterns that indicate that cell plasma membranes were intact during tissue incubation in the device. 24,[26][27][28][70][71][72] Secondly, we showed that the cytokines released by GBM tissues in the device remained the same for the duration of the experiment. We assayed the levels of 105 cytokines in the effluents corresponding to days 2, 4 and 8 of incubation.…”
Section: Maintaining Fresh Gbm Biopsies In a Viable Condition In The ...mentioning
confidence: 70%
“…These are well-known patterns that indicate that cell plasma membranes were intact during tissue incubation in the device. 24,26–28,70–72…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not found sensitivity to be an issue with cells and tissue maintained in other devices we have developed; preliminary investigations confirmed that IL-6 was reliably detected (data not shown). Similar devices used by Riley et al (2021) also successfully identified a panel of factors in effluent using a Proteome Profiler (Biotechne, Abingdon, Oxford). If biomarker release was determined to be too low it is possible to concentrate the effluent, however there are limitations to this as additives to cell medium such as serum can interfere with any subsequent assays once concentrated.…”
Section: Discussionmentioning
confidence: 99%